The Effect of Mental Health Intervention before English Test on College Students’ English Test Scores - Yan Sun (Occupational Therapy International, 2022)
It is necessary to pay attention to and study the physical and mental health development of college students. On the basis of statistical analysis of the questionnaire, this paper studies the impact of pretest mental health intervention on college students’ English test scores, summarizes the problems and characteristics of college students’ mental health, and explores the reasons for psychological problems. Based on the research results and related survey data of the mental health status of college students by scholars, this paper believes that these reasons mainly include students’ personal reasons, school and social environment pressure, and insufficient family support factors. The data analysis shows that in the relationship between English education and mental health in colleges and universities, the amount of mental health intervention of students’ extracurricular exercise has a stable and low negative correlation with the scores of each factor of SCL-90 (Symptom Checklist 90) and is negatively correlated with the scores of each subscale. The experimental results show that there are extremely significant differences in academic performance (F=5.084, P<0.01), and there is a certain linear relationship between students’ mental health level and students’ English exercise feeling. The lower the fatigue score, the higher the mental health level of the students, which effectively promotes the mental health development of college students.